Pengembangan Materi Pembelajaran Bahasa di Sekolah Dasar - Amini Amini; Dea Rahma Damanik; Zakiyah Andiny Sihombing; Vita Shahnaz Maharani Rangkuti; Rinaldi Rusli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Teaching materials are one of the important things in teaching and learning activities. To design learning, it is necessary to consider what kind of teaching and learning materials are needed to achieve learning objectives and achieve the required abilities, and for this reason it is necessary to develop teaching materials. In developing teaching materials, we can refer to two things: the context in which education takes place and the form of learning activities that take place. Contextual considerations are made to determine the packaging format for learning materials. For example, whether students bond with each other. Regarding the format of learning activities, teachers need to consider whether traditional teaching, distance learning, or a combination of both. Five factors must be considered when developing learning materials: student characteristics, format of learning activities, context in which training takes place, learning strategies, and tools for assessing learning outcomes.